2013
DOI: 10.4236/health.2013.512a011
|View full text |Cite
|
Sign up to set email alerts
|

Elderly vaccination—The glass is half full

Abstract: The shifting global demography and ageing of populations worldwide brings with new challenges for the health care, and an imperative for healthy ageing and preventive health strategies for adults. Immunization is the low hanging fruit for healthy ageing, and yet under-utilized for various reasons, including waning immunity in the elderly, lack of RCT data in this age group, and lack of provider confidence in vaccines for the elderly. The elderly people have a higher incidence of infection and more severe and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Decisions around vaccination are complicated by evidence of decreasing efficacy against zoster incidence based on age at vaccination [ 27 ] and waning in efficacy against zoster burden based on time since vaccination [ 30 ]. Waning of vaccine-induced immunity occurs with most vaccines and reflects the natural phenomenon of immunosenescence [ 54 ]. Waning of vaccine-induced immunity is critically important for infant vaccination, who have a full lifespan ahead of them, but is less important for the elderly, when expected lifespan is short.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Decisions around vaccination are complicated by evidence of decreasing efficacy against zoster incidence based on age at vaccination [ 27 ] and waning in efficacy against zoster burden based on time since vaccination [ 30 ]. Waning of vaccine-induced immunity occurs with most vaccines and reflects the natural phenomenon of immunosenescence [ 54 ]. Waning of vaccine-induced immunity is critically important for infant vaccination, who have a full lifespan ahead of them, but is less important for the elderly, when expected lifespan is short.…”
Section: Discussionmentioning
confidence: 99%
“…Waning of vaccine-induced immunity is critically important for infant vaccination, who have a full lifespan ahead of them, but is less important for the elderly, when expected lifespan is short. The value of vaccines is a function of both immunogenicity and disease burden, and elderly vaccines should be considered within this equation [ 54 ]. Despite lower efficacy with age, HZ vaccination may have value in the older elderly because of higher disease burden [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite influenza vaccine being recommended in many countries for patients with CVD [22], it has not made its way into practice as a routine measure to protect patients at risk, with vaccination rates in patients with CVD being low [23]. It has been shown that clinicians in general have a low awareness of adult vaccination and are not strong advocates for vaccination in adults [24,25]. Improved clinician awareness of the benefits of influenza vaccine in prevention of CVD events is needed to take advantage of vaccination as low-hanging fruit for prevention of AMI.…”
Section: Resultsmentioning
confidence: 99%